All Days 1999
DOI: 10.2118/50730-ms
|View full text |Cite
|
Sign up to set email alerts
|

Slaying the Myth of Infinite Reactivity of Carbonates

Abstract: The simplifying assumption that limestones essentially have infinite reactivity has been a powerful and useful tool in helping our industry understand and model the acidizing process of carbonate formations. However, over the past few years, considerable work has shown that this assumption need not be used. In fact, use of this assumption can lead to incorrect conclusions regarding optimized acidizing of carbonate formations. This paper builds upon the historical foundation of understanding the acidizing proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…A temperature survey performed subsequent to the acid treatment indicated the temperature was 158 o F, and the falloff test indicated a BHST of 156 o F. The Arab-D is a dolomitic limestone, and dolomite reacts with HCl under surface reaction kinetics at a temperature less than 175 o F. 16 Recently it was reported that the energy of activation of dolomite was twice that of limestone. 25 This is indicative of a slower reaction, which is supported in the literature. 1 Thus, the acid may preferentially bypass the dolomite and wormhole through the limestone to create deeper penetration.…”
Section: Resultssupporting
confidence: 75%
“…A temperature survey performed subsequent to the acid treatment indicated the temperature was 158 o F, and the falloff test indicated a BHST of 156 o F. The Arab-D is a dolomitic limestone, and dolomite reacts with HCl under surface reaction kinetics at a temperature less than 175 o F. 16 Recently it was reported that the energy of activation of dolomite was twice that of limestone. 25 This is indicative of a slower reaction, which is supported in the literature. 1 Thus, the acid may preferentially bypass the dolomite and wormhole through the limestone to create deeper penetration.…”
Section: Resultssupporting
confidence: 75%
“…Although the implications of these results for acidizing treatments were evaluated, the underlying cause was not addressed. Reaction rate reduction caused by clays will be discussed in this paper that can explain the results reported by Gdanski and van Domelen (1999).…”
Section: Introductionmentioning
confidence: 59%
“…Anderson showed that significant variations in reactivity existed, but did not explain or investigate the results. Gdanski and van Domelen (1999) reported that carbonate reservoir rocks were often significantly less reactive at reservoir conditions than would be expected from reactivity data reported for pure calcite marble and dolomite marble as given by Lund et al (1973Lund et al ( , 1975. Although the implications of these results for acidizing treatments were evaluated, the underlying cause was not addressed.…”
Section: Introductionmentioning
confidence: 98%
“…This instrument has been used extensively to investigate the reaction of HCl, organic acids, and chelating agents with carbonate rocks (Hansford and Litt 1968;Lund et al 1975;de Rozieres et al 1994;Fredd and Fogler 1998a, 1998b, 1998cFredd 1998;Conway et al 1999;Gautelier et al 1999;Gdanski and Van Domelen 1999;Frenier and Hill 2002;Taylor et al 2004aTaylor et al , 2004bTaylor et al , 2006Alkattan et al 1998Alkattan et al , 2002Al-Mohammad et al 2006;Al-Khaldi et al 2007;Nasr-El-Din et al 2008b). It has also been used to study mass and heat transfer in non-Newtonian fluids (Hansford and Litt 1968;de Rozieres et al 1994;Al-Mohammad et al 2006;Nasr-El-Din et al 2008b).…”
Section: Introductionmentioning
confidence: 99%